Answer:
x = 1
Explanation:
We are to find the solution of the following logarithmic equation:
![ln ( x ) + l n ( x ) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tpogdrf6jqrqppimkhkbl1mqvrpbs9kpf5.png)
We will add the similar elements to get:
![2 l n ( x ) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1xbqs7kftccuvbuatti52gj0t2y8lpl4pt.png)
Dividing both sides by 2 and simplify to get:
![\frac { 2 l n ( x ) } { 2 } = \frac { 0 } { 2 }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uhn99f16movl6ldid92j512jcdz1apg1n9.png)
![ln(x)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ij37z3kh8wdkhrizg5qb82iantrpny0p4o.png)
Applying the rule
to get:
![0=ln(e^0)=ln(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/seuvmtlv9flme2kr2b6zyndn5okoob6ey5.png)
![ln(x)=ln(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9rzj232kp5ya6jiymk56lom9ushkioihl9.png)
Here the logs have the same base, so:
x = 1